2007
DOI: 10.1200/jco.2007.25.18_suppl.1109
|View full text |Cite
|
Sign up to set email alerts
|

Dose scheduling and pharmacokinetic (PK) study of trastuzumab in patients (pts) with HER2/neu overexpressing breast cancer?

Abstract: 1109 Has been demonstrated that 10–20 μg/mL is the minimum serum trough concentration (Cmin) of trastuzumab that causes maximal tumor growth inhibition. This concentration was shown to be achievable using a weekly (4 mg/kg loading dose followed by 2 mg/kg weekly) and a three-weekly (8 mg/kg loading dose followed by 6 mg/kg) schedule, but only indirect comparisons of the two schedule have been performed. We prospectively analysed the PK distribution of trastuzumab in three different schedules, as follows: week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…10,13 Tratuzumab dosing in bi-weekly schedules is different, albeit there are data that suggest that these dosages are capable of reaching the minimum concentrations associated with inhibition of tumor growth. 31 One possible cause for this advantage in the AGAMENON registry is that by using ToGA or CAPOX-T regimens, there was a tendency to assume that the treatment had a pre-defined duration as considered for the CF or XP regimens, while with FOLFOX-T, FU may have been managed differently, which facilitated maintenance together with trastuzumab. Optimal treatment duration has not been well defined in advanced gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…10,13 Tratuzumab dosing in bi-weekly schedules is different, albeit there are data that suggest that these dosages are capable of reaching the minimum concentrations associated with inhibition of tumor growth. 31 One possible cause for this advantage in the AGAMENON registry is that by using ToGA or CAPOX-T regimens, there was a tendency to assume that the treatment had a pre-defined duration as considered for the CF or XP regimens, while with FOLFOX-T, FU may have been managed differently, which facilitated maintenance together with trastuzumab. Optimal treatment duration has not been well defined in advanced gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the study by Carter et al 16 seemed to plateau at 8-10 mg/mL, while Tokuda et al 13 suggested plateauing at 0.1-1.0 mg/mL from their data. However, subsequent clinical trials generally aimed for serum levels of >10-20 mg/mL 9,10,[12][13][14][15] and none was designed to achieve >50 mg/mL. A steady state of serum level is reached for the weekly and three-weekly dosing after 20 and 12 weeks, respectively.…”
mentioning
confidence: 99%